Efficacy Comparison of Six Chemotherapeutic Combinations for Osteosarcoma and Ewing's Sarcoma Treatment: A Network Meta‐Analysis. Issue 1 (4th October 2017) - Zhang, Tao; Zhang, Song; Yang, Feifei; Wang, Lili; Zhu, Sigang; Qiu, Bing; Li, Shunhua; Deng, Zhongliang
ABSTRACT: This study aimed to address the insufficiency of traditional meta‐analysis and provide improved guidelines for the clinical practice of osteosarcoma treatment. The heterogeneity of the fixed‐effect model was calculated, and when necessary, a random‐effect model was adopted. Furthermore, the direct and indirect evidence was pooled together and exhibited in the forest plot and slash table. The surface under the cumulative ranking curve (SUCRA) value was also measured to rank each intervention. Finally, heat plot was introduced to demonstrate the contribution of each intervention and the inconsistency between direct and indirect comparisons. This network meta‐analysis included 32 trials, involving a total of 5, 626 subjects reported by 28 articles. All the treatments were classified into six chemotherapeutic combinations: dual agent with or without ifosfamide (IFO), multi‐agent with or without IFO, and dual agent or multi‐agent with IFO and etoposide. For the primary outcomes, both overall survival (OS) and event‐free survival (EFS) rates were considered. The multi‐agent integrated with IFO and etoposide showed an optimal performance for 5‐year OS, 10‐year OS, 3‐year EFS, 5‐year EFS, and 10‐year EFS when compared with placebo. The SUCRA value of this treatment was also the highest of these six interventions. However, multi‐drug with IFO alone had the highest SUCRA value of 0.652 and 0.516 when it came to relapse and lung‐metastasis. It was efficient to some extent, but no significant difference was observed in both outcomes. Chemotherapy, applied as induction or adjuvant treatment with radiation therapy or surgery, is able to increase the survival rate of patients, especially by combining multi‐drug with IFO and etoposide, which demonstrated the best performance in both OS and EFS. As for relapse and the lung‐metastasis, multiple agents with IFO alone seemed to have the optimal efficiency, although no significant difference was observed here. J. Cell. Biochem. 119: 250–259, 2018. © 2017 Wiley Periodicals, Inc. Abstract : Chemotherapy, applied as induction or adjuvant treatment with radiation therapy or surgery, is able to increase the survival rate of patients, especially by combining multi‐drug with IFO and etoposide, which demonstrated the best performance in both OS and EFS. As for relapse and the lung‐metastasis, multiple agents with IFO alone seemed to have the optimal efficiency, although no significant difference was observed here.